Florida Carpenter Ant, Bull Ant, Tortugas Carpenter Ant, Camponotus floridanus (Buckley) and Camponotus tortuganus (Emery) (Insecta: Hymenoptera: Formicidae: Subfamily ormicinae: Tribe Camponotini) - John Warner; Rudolf H. Scheffrahn (EDIS, 2004)
The Florida carpenter ant complex is comprised of several species, two of which are common around structures: Camponotus floridanus (Buckley) and Camponotus tortuganus (Emery). These bicolored arboreal ants are among the largest ants found in Florida, making them apparent as they forage or fly indoors and out. This document is EENY-272, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 2002. Revised: September 2004.